Desempenho empresarial em crises globais: uma análise da volatilidade e retornos das ações, e do desempenho financeiro das empresas da B3, no Início da guerra russo-ucraniana e da pandemia da Covid-19 - Letícia Drummond Rezende (2024)
The Covid-19 pandemic has had significant effects on global economies, shaking the markets due to strategies to contain the disease that have impacted production and consumption. In March 2020, the world's stock markets faced abnormal volatility, reflected, for example, in the successive circuit breaker triggers, as occurred in Brazil. Two years after the start of the pandemic, when nations were recovering from the health and economic damage caused by the new Coronavirus, a new crisis arose with the Russian invasion of Ukrainian territory. This conflict also caused economic crises on the international stage, due to the trade sanctions imposed on Russia. In the context of these crises for global economies, the general objective of this thesis was to investigate whether the first few months of the Covid-19 crisis and the war between Russia and Ukraine had an impact on the financial performance, price volatility and return on shares of Brazilian listed companies. The thesis consists of three articles, which analyze each of these three perspectives, i.e. the financial performance, prices and returns of the shares of companies listed on the Brazilian stock exchange (B3). The first article identified and analyzed the relationship between information about the war in Ukraine and company stock returns. Based on the Efficient Market Hypothesis (EMH), the methodology used was an event study which investigated the effect of the conflict on stock returns, checking whether markets are efficient, i.e. whether these returns reflect all the information available in times of crisis. The results indicated that the war had no relevant impact on B3 stock returns. The second article evaluated the volatility of the share prices of B3 companies, considering the start of the Covid-19 crisis, in the period between January/2020 and May/2020. The analysis, based on Markowitz's Modern Portfolio Selection Theory, used the autoregressive conditional heteroscedasticity (ARCH) modeling methodology. The results showed that all sectors showed clusters of volatility, with the technology and health sectors showing the most intense volatility in mid-March/2020; this suggested more significant impacts of the pandemic on these sectors at the worst moment of the health and economic crisis. The third article analyzed the financial performance of Brazilian companies between January 2019 and March 2023 in response to the Covid-19 and Russian-Ukrainian War crises. The methodology used was panel data analysis. The results suggested that both crises had an impact on companies' financial performance, which was more intense in the initial period of the pandemic. One contribution of this research was to validate the HME in practice by studying events on the stock market's response to news related to global crises. The empirical evidence on the effects of the Covid-19 pandemic and the war in Ukraine on the financial markets analyzed contributes to knowledge about these events and their impacts on company performance. In practice, such knowledge provides investors and organizations with insights to assess the risks and opportunities in geopolitical crisis scenarios, helping them to better understand and manage the financial risks associated with similar events in the future, as well as to make more rational and planned investment decisions. In this sense, understanding how markets react to critical events can provide input for companies' strategic planning, with the aim of adapting their business strategies according to the economic environment in times of uncertainty and sudden change.